Practising Peer Observation: Bringing Out the Best in EFL Teachers' Collaboration in Saudi Arabia - Asiri, Wejdan (2018)
The current study aims at investigating the perceptions of EFL teachers on the peer observation of teaching in schools in Saudi Arabia. It has reviewed the literature of collaboration among teachers and professionalism through practising peer observation to develop an overview of models of teachers’ learning and professionalism. This research has adapted a mixed method approach to elicit both qualitative and quantitative data obtained from 48 female EFL teachers working in several government and international schools in Saudi Arabia. The main finding from the questionnaire indicated a high level of positive attitude towards the implementation of peer observation in Saudi schools. Additionally, questionnaire data and the thematic analysis of the qualitative data, presented in four primary themes, concluded that peer observation is an effective practice that could improve the EFL teaching quality in Saudi Arabia. However, peer observation is still not widely implemented practice in the Saudi schools for number of reasons and barriers. Thus, based on the study’s findings, number of recommendations are presented in an attempt to increase the awareness of the Saudi EFL teachers on the effectiveness of the process of peer observation to be implemented appropriately.